2014
DOI: 10.1080/09602011.2014.971820
|View full text |Cite|
|
Sign up to set email alerts
|

A meta-synthesis of qualitative research on perceptions of people with long-term neurological conditions about group-based memory rehabilitation

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. AbstractThe effectiveness of memory rehabilitation based on randomised controlled trials and metaanalyses has been inconclusive, but patient reports based on qualitative studies have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
(34 reference statements)
1
11
1
Order By: Relevance
“…Only English language articles were included. This is in keeping with recently published meta-ethnographies [26].…”
Section: Identifying Relevant Papers For Inclusionsupporting
confidence: 69%
See 1 more Smart Citation
“…Only English language articles were included. This is in keeping with recently published meta-ethnographies [26].…”
Section: Identifying Relevant Papers For Inclusionsupporting
confidence: 69%
“…Based on seminal and more recent published examples of the process [21,[23][24][25][26], the present meta-ethnography comprised three steps: (i) identifying relevant papers for inclusion, (ii) critical appraisal and data extraction, and (iii) analysis and synthesis of findings.…”
Section: Methodsmentioning
confidence: 99%
“…In a metasynthesis of qualitative research on perceptions of people participating in group-based cognitive rehabilitation, das Nair et al [16] found that cognitive rehabilitation was associated with increased confidence, self-awareness, and learning of new skills and strategies to compensate for deficits. Additionally, they found that those changes had a positive impact on daily life in personal and professional spheres [16].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive rehabilitation is a structured set of therapeutic activities designed to retrain or compensate for an individual's impaired cognitive abilities (Tsaousides & Gordon, 2009;dasNair, Martin, & Sinclair, 2015). However, the evidence for the effectiveness of cognitive rehabilitation for people with MS is mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous meta-syntheses of cognitive rehabilitation focused on people with stroke (Reed, Wood, Harrington, & Paterson, 2012) and long-term neurological conditions in general (dasNair et al, 2015). The latter meta-synthesis was limited to group-based rehabilitation programmes.…”
Section: Introductionmentioning
confidence: 99%